2015
DOI: 10.1002/jaal.444
|View full text |Cite
|
Sign up to set email alerts
|

Writing Instruction for Adolescents in the Shadow of the Common Core State Standards

Abstract: Current research on instructional practices for secondary student writing reveals little emphasis on compositions requiring analysis, interpretation, and argumentation. Indeed, written expression in English language arts classes is generally confined to writing assignments of very limited length. Additionally, recent efforts for educational reform have led the United States to adopt national academic standards. This article examines the current focus on composition instruction for secondary students as girded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
0
7
0
4
Order By: Relevance
“…The importance of exposure to reading materials is emphasised in many studies. Sundeen (2015) argues that pupils read far too little, and instead of completing countless worksheets they should read across the whole curriculum, discuss what they are reading and write much more about it than they do. It is indicated that through these tasks they might develop not only their literacy skills but also their academic skills and vocabulary.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of exposure to reading materials is emphasised in many studies. Sundeen (2015) argues that pupils read far too little, and instead of completing countless worksheets they should read across the whole curriculum, discuss what they are reading and write much more about it than they do. It is indicated that through these tasks they might develop not only their literacy skills but also their academic skills and vocabulary.…”
Section: Discussionmentioning
confidence: 99%
“…We know the tests will substantially influence our curriculum and instruction (Sundeen, 2015). But at what cost?…”
Section: Limitationsmentioning
confidence: 99%
“…Bu noktada öğretmen yeterlikleri, öğretmenlerin yazma güçlüğüne ilişkin bakış açıları, sınıf içi uygulamaları ve konu ile ilgili bilgileri ön plana çıkmaktadır. Çünkü öğretmenlerin bu konudaki deneyimleri, bilgileri ve kendilerini yeterli görme düzeyleri bu sorunun ortadan kaldırılmasında önemli rol oynar (Graham, Harris, Bartlett, Popadopoulou ve Santoro, 2016;Sundeen, 2015). Buradan hareketle sınıf öğretmenlerinin yazma güçlüğüne ilişkin görüşleri önem kazanmaktadır.…”
Section: Gđrđşunclassified
“…Bu noktada araştırmaya katılan öğretmenlerin yaptıkları çalışmaların yerinde olduğu söylenebilir. Ancak günümüzde hala birçok öğrencinin kompozisyon yazmakta güçlük çektiği düşünüldüğünde (Sundeen, 2015), sınıfta veya evde yapılacak tekrarlı yazma çalışmalarından farklı olarak öğrencilerin yazma gelişimlerini doğrudan etkileyecek değişik uygulamalara da yer verilmesi gerektiği söylenebilir. Bu bağlamda planlı bir şekilde yürütülen stratejik çalışmalardan daha fazla yararlanmak, yazma güçlüğü olan öğrencilerin gelişimlerine katkı sağlayabilir (Saddler, Moran, Graham ve Harris, 2004).…”
Section: Tartişma Sonuç Ve öNerđlerunclassified
See 1 more Smart Citation